Kajian Intertekstualitas Sampul Album 'Viva La Vida' dari Coldplay - Brian Alvin Hananto (DeKaVe, 2019)
Every design objects had meanings that borrowed their meanings from other texts. This understanding comes from the notion of intertextuality, in which this notion isn’t absent from graphic design. This article will discuss about the design of Coldplay’s 2008 ‘Viva La Vida’ album cover design. The study for the design will be done in two ways, in a formalistic manner which elaborates the design and visual elements of the design, and also in a contextual manner which discusses the meanings that come from external texts. The study is approached with a qualitative perspective, using the artifact analysis and literature review method. The result of the study is the conclusion that ‘Viva La Vida’ had borrowed references from other popular texts that enriches the value of the design. The author hoped that this writing can open up new perspective on how to see graphic design objects.